Társasági üzletrész értékelése házastársi vagyonmegosztási perekben Szakértői bizonyítás – Szakértői kompetencia - Csirmaz, László (Debreceni Jogi Műhely, 2014)
New types of assets has appeared in property lawsuits in the past 25 years, such as company shares (one of the most important kind of valuable rights). This fact made forensic experts - who deal with evaluation of these assets - to obtain additional comprehensive knowledge.  The Kuria quoted that "the expert opinion is an underlying proof for the court judgment, an objective and precise means of proof, which usually affects directly the decisions of the court," and I think the date of the completion of the trial can be affected significantly.The author of the study and writing of the addition was designed to court pointed out weaknesses in the analyzed case by case decisions perceived peer involvement draws the attention of the interested public on the company's assessment of literature on the importance of knowledge. To that aim the light of the experience gained from the analysis of the case law, above all, the study seeks to publish the company's fundamental valuation basic concepts summarize the literature on the same value in generally accepted and applied definitions and outline the applicable assessment methods. It is certain that the regulation of property relations in the new Code requires the renewal of judicial regulation of professional activity as well.